RADIOGRAPHY OF THE RIGHT ELBOW JOINT WITH SUSPENSION ARTHRITIS AT MEDAN HAJI GENERAL HOSPITAL - Justinus Tambunan; Juliana Lasniar Sidauruk (Yayasan Nuraini Ibrahim Mandiri, 2025)
Elbow Joint is the joint between the radius-ulna and the humerus. The Elbow Joint examination technique is a radiological examination to see clinical or disease around the elbow joint. In the clinical there is a disease called Arthritis which is inflammation of the joints, especially in the elbow joint. The purpose of this study was to determine the Elbow Joint examination technique and the results of the Elbow Joint radiograph image with clinical arthritis at the Radiology Installation of Medan Haji General Hospital in May 2025, using an x-ray machine with a capacity of 500 mA, but the author only used 100 mA to obtain optimal image sharpness. This study uses a qualitative method, data collection is carried out through observation techniques, and consultations with radiology specialists, and discussions with radiographers, as well as documentation and library studies. The collected data are then analyzed to obtain conclusions. The results of the study show that the Elbow Joint examination technique in clinical arthritis uses two projections, namely Antero posterior and Lateral. through image processing using Computer Radiography (CR). In the lateral projection, the object position is not correct due to the patient's stiff condition. However, the radiograph results produced show a fairly clear anatomical image, so they can help establish a diagnosis.